INSTALASI RUNNING TEXT DI PINTU MASUK KAMPUNG BAMBU MEWEK RW 04 KEL. TUNJUNGSEKAR, KEC. LOWOKWARU, KOTA MALANG - Heryanto Heryanto; Sadar Wahjudi; Maskuri Maskuri; Anggit Murdani; Agus Hardjito (Publisher UPT P2M Politeknik Negeri Malang, 2019)
The residents of RW.04 Kelurahan Tunjungsekar have a plan to create a public playground called Kampung Bambu Mewek. The lack of funding for the development of Bamboo Mewek Village has an impact on the lack of facilities it has. This is seen one of them is the entrance to Kampung Bamboo Mewek that not too impressed so less attract people to visit it. Through this PkM program, it is proposed to install running text, so it is expected to attract people to visit Kampung Bambu Mewek. The method of implementation of this community service program is together with the community building gate of Kampung Bambu Mewek. Some stages of the implementation of this program are: 1. Preparation stage, at this stage we have done first for the preparation of equipment and materials needed such as: Running Text. 2. Erection stage, at this stage in mutual cooperation with the community to build the gate Kampung Bambu Mewek. 3. Reporting stage, at this stage will be reported the results of activities that have been implemented including details of the cost. The whole stages are conducted over a period of 1 month involving the role of the civilitation RT.09 RW.04 Kel. Tunjungsekar Kota Malang.